Comparisons of the TOMS aerosol index with Sun-photometer aerosol optical thickness: Results and applications - Hsu, N. C.; Herman, Jay; Torres, O.; Holben, B. N.; Tanre, D.; Eck, Thomas; Smirnov, A.; Chatenet, B.; Lavenu, F. (AGU, 1999)
A nearly 20-year global data set (1979–1994 and 1996 to the present) of tropospheric absorbing aerosols has been developed from total ozone mapping spectrometer (TOMS) backscattered radiance measurements in the range from 331 to 380 nm. The occurrence of aerosols is derived directly from measured backscattered radiances and is represented by a quantity known as the aerosol index. Previous theoretical model simulations have demonstrated that the aerosol index depends on aerosol optical thickness (AOT), single scattering albedo, and aerosol height and that the AOT can be determined provided that the microphysical properties and height of aerosols are known. In this paper we show that the TOMS aerosol index measurements are linearly proportional to the AOT derived independently from ground-based Sun-photometer instruments over regions of biomass burning and regions covered by African dust. We also show how this linear relationship can be used to directly convert the aerosol index into AOT for smoke and dust aerosols for the regions near the Sun-photometer sites and how information about aerosol height can be inferred from the results. Finally, we apply this method to the TOMS data over the last two decades and find a significant increase in the amount of biomass burning smoke in the African savanna regions during the 1990s in addition to the more obvious increase in South America.
Comparisons of the TOMS aerosol index with sun photometer aerosol optical thickness